THE INFLUENCE OF MARKETING MIX ON PURCHASING DECISIONS OF U WINFLY BRAND ELECTRIC MOTORCYCLES AT ARKA BIKE - Al’asqolaini, Muchsin Zuhad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
Along with technological advances and the times, Marketing is one of the most important parts in advancing a company, especially companies engaged in goods and services. In the business world, every company is required to compete and formulate the right marketing strategy. The purpose of this study was to determine the effect of the marketing mix consisting of product, price, promotion, and place on the purchasing decision of U Winfly electric motorcycle at Arka Bike Gresik. This research is quantitative research. The population in this study are consumers at Arka Bike Gresik with a total sample of 60 respondents. This studi uses multiple linear regression analysis technique. The results of the analysis show that the marketing mix which consists of product, price, promotion and place simultaneously has a significant effect on purchasing decisions, while partially the marketing mix consisting product, place and pomotion have a significant effect on motorcicles purchasing decisions U Winfly brand electric motorbike at Arka Bike Gresik but not for price variable.